HIGH-EFFICIENCY NANOPOROUS ADSORBENT IN GOLD EXTRACTION (Comprehensive Journal of Science, 2025)
We report the development of MP-HMS (Mercaptopropyl–Hexagonal Mesoporous Structure), a high-capacity nanoporous adsorbent for gold extraction, designed using nanotechnology. By incorporating thiol groups into the pores of mesoporous silica, MP-HMS can efficiently capture gold ions from ultra-dilute solutions, including mine effluents and leachates from gold mills. Laboratory tests with simulated gold solutions show exceptional adsorption capacities, with up to 370 mg of gold per gram of material (≈37% of its weight) and recovery rates as high as 99.9%. Ongoing studies focus on the interaction of ionic gold complexes with these nanomaterials. Future applications may allow MP-HMS to either supplement or replace conventional CIP/CIL processes, offering a novel approach to gold extraction in pulp (MIP) or leach (MIL) systems.Key Words: Nanotechnology, gold ion extraction, effluent treatment, ultra-low concentration, high-capacity nanoporous adsorbents.
Keywords: Nanotechnology, gold ion extraction, effluent treatment, ultra-low concentration, high-capacity nanoporous adsorbents.